2014
DOI: 10.1111/cpf.12116
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between carotid intima–media thickness and global atherosclerosis

Abstract: BackgroundThe aim of this study was to investigate the relationship between (i) carotid intima–media thickness (CIMT) at baseline as well as (ii) change in CIMT over 5 years (ΔCIMT) and atherosclerotically induced luminal narrowing in non-coronary arterial territories assessed by whole-body magnetic resonance angiography (WBMRA).Methods and resultsIn subgroups of the Prospective Investigation of Vasculature in Uppsala Seniors (PIVUS) study, US measurements of CIMT in the common carotid arteries were analysed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The research by Veller et al 22 reported that, among individuals whose CIMT was greater than 0.8 mm, 95.5% had plaque in their aorta. The research by Lundberg et al 29 suggested that CIMT was related to overall stenoses in the body, even after adjustment for traditional risk factors, confirming CIMT as an indicator of general atherosclerosis. Taken together, the independent correlation between CIMT and PTT in the thickened CIMT hypertensive group may suggest that rcPTT and acPTT could be useful adjunctive markers in reflecting the degree of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…The research by Veller et al 22 reported that, among individuals whose CIMT was greater than 0.8 mm, 95.5% had plaque in their aorta. The research by Lundberg et al 29 suggested that CIMT was related to overall stenoses in the body, even after adjustment for traditional risk factors, confirming CIMT as an indicator of general atherosclerosis. Taken together, the independent correlation between CIMT and PTT in the thickened CIMT hypertensive group may suggest that rcPTT and acPTT could be useful adjunctive markers in reflecting the degree of atherosclerosis.…”
Section: Discussionmentioning
confidence: 93%
“…Our results match with data from the medical literature. [6][7][8] From our data, we can state that the most severely affected coronaries were found in the diabetes group. The same result was found in similar studies.…”
Section: Discussionmentioning
confidence: 96%
“…TAS is related to IMT in the PIVUS population, with a significant relationship ( P = 0·0001) even after adjusting for traditional cardiovascular risk factors (Lundberg et al ., ). It has been claimed that increased IMT is more likely to be caused by hypertension, rather than being part of the atherosclerotic plaque process.…”
Section: Discussionmentioning
confidence: 97%